Enterprise Resource Planning and Firm Value: Case of Oil and Gas Firm in Indonesian Stock Exchange - Nur, D.P. Emrinaldi; Putra, Adhitya Agri (International Journal of Energy Economics and Policy, 2020)
Since oil price crash has big impact on oil and gas firm value, it is important to implements information technology for value improvement, such as enterprise resource planning implementation. This research is aimed to examine the effect of enterprise resource planning implementation on oil and gas firm value. Research sample are oil and gas firms which listed in Indonesian Stock Exchange 2013-2018. Enterprise resource planning implementation is measured by dummy variable. Firm value is measured by return on assets and market to assets value. Based on random effect regression analysis, enterprise resource planning implementation increases firm value. Enterprise resource planning provides higher information quality, integrated relationship between firms' functions and departments, integrated relationship between supplier and customer, also efficiency in resource usage. Keywords: enterprise resource planning, firm value, Indonesian stock exchange, oil and gas, return on assets, market to assets value JEL Classifications: M15, O33, Q40 DOI: https://doi.org/10.32479/ijeep.10044